Pengaruh Electronic Word of Mouth terhadap Keputusan Pembelian Sunscreen Wardah di Shopee pada Mahasiswi Program Studi Tata Rias dan Kecantikan FPP UNP - Aura Ashfahani; Vici Syahril Chairani (Lembaga Yasin AlSys, 2026)
Although online reviews, ratings, and comments are increasingly used as sources of information when purchasing beauty products, the role of electronic word of mouth (e-WOM) in shaping Wardah sunscreen purchase decisions through Shopee still requires further investigation. This study aimed to analyze the effect of e-WOM on Wardah sunscreen purchase decisions among female students in the Cosmetology and Beauty Study Program at FPP UNP. The study employed a quantitative approach with a descriptive-explanatory design. Data were collected through questionnaires administered to female students who met the sampling criteria and were analyzed quantitatively. The results showed that e-WOM, particularly source credibility, review quantity, review valence, and argument quality, was associated with improved purchase decisions. Respondents also tended to use product reviews as references before making purchases. These findings confirm that e-WOM plays an important role in shaping consumer purchase decisions in marketplaces. In practical terms, sellers need to maintain product quality and encourage the development of credible positive reviews, while consumers need to be more selective in evaluating online information before making purchase decisions.